An Inclusive Distance Irregularity Strength of n-ary Tree - Wijaya, Kristiana; Aulia, Safira Nur; Halikin, Ikhsanul; Kusbudiono, Kusbudiono (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
An inclusive distance vertex irregular labelling of a simple graph G is a function of the vertex set of  to positive integer set such that the sum of its vertex label and the labels of all vertices adjacent to the vertex are distinct. The minimum of maximum label of the vertices is said to be inclusive distance irregularity strength of G, denoted by dis(G). The purpose of this research is showing that dis(T_{n,2})= (n^2+2)/2 where T_{n,2} is a complete n-ary tree to level two.